PENERAPAN MEDIA GAME EDUKASI BERBASIS SMARTBORT DALAM PEMBELAJARAN MENULIS AKSARA JAWA DI SMP - Prasetyo, Daniel Dwi; Alfiah, Alfiah; Sunarya, Sunarya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Javanese script as a cultural heritage is currently threatened with extinction due to the lack of interest and innovation in learning, particularly at the junior high school level. This study aims to describe the implementation of smartboard-based educational game media and examine students' responses in learning to write Javanese script in grade VII of SMP Negeri 2 Donorojo. The method used is descriptive qualitative with an implementation study design. Data were collected through post-test and questionnaire instruments from 22 students and analyzed using the percentage technique based on Riduwan's (2013) assessment classification. The results show that the students' average post-test score reached 84.90 with a classical completeness rate of 100%, categorized as "Very Good." All students successfully exceeded the minimum competency criterion (KKM) of 75. Students' responses toward the media were also highly positive, marked by high enthusiasm, increased learning motivation, and greater ease in understanding and writing Javanese script. The interactivity of the smartboard and competitive elements in the game were key factors driving active student engagement. This study concludes that smartboard-based educational game media is effective as an innovative learning alternative that supports the preservation of Javanese culture through formal education.